Proanthocyanidins mitigate bile acid‐induced changes in GSTT2 levels in a panel of racially diverse patient‐derived primary esophageal cell cultures. Issue 3 (10th November 2021) - Weh, Katherine M.; Turgeon, Danielle K.; Rubenstein, Joel H.; Clarke, Jennifer L.; Howell, Amy B.; Chang, Andrew C.; Kresty, Laura A.
Abstract: Persistent and symptomatic reflux of gastric and duodenal contents, known as gastroesophageal reflux disease (GERD), is the strongest risk factor for esophageal adenocarcinoma (EAC). Despite similar rates of GERD and other risk factors across racial groups, EAC progression disproportionately impacts Caucasians. We recently reported that elevated tissue levels of the detoxification enzyme GSTT2 in the esophagi of Blacks compared to Caucasians may contribute protection. Herein, we extend our research to investigate whether cranberry proanthocyanidins (C‐PAC) mitigate bile acid‐induced damage and GSTT2 levels utilizing a racially diverse panel of patient‐derived primary esophageal cultures. We have shown that C‐PACs mitigate reflux‐induced DNA damage through GSTT2 upregulation in a rat esophageal reflux model, but whether effects are recapitulated in humans or differentially based on race remains unknown. We isolated normal primary esophageal cells from Black and Caucasian patients and assessed GSTT2 protein levels and cellular viability following exposure to a bile acid cocktail with and without C‐PAC treatment. Constitutive GSTT2 levels were significantly elevated in Black (2.9‐fold) compared to Caucasian patients, as were GSTT2 levels in Black patients with GERD. C‐PAC treatment induced GSTT2 levels 1.6‐fold in primary normal esophageal cells. GSTT2 induction by C‐PAC was greatest in cells with constitutively low GSTT2 expression. Overall, C‐PAC mitigated bile‐induced reductions of GSTT2 and subsequent loss of cell viability regardless of basal GSTT2 expression or race. These data support that C‐PAC may be a safe efficacious agent to promote epithelial fitness through GSTT2 induction and in turn protect against bile acid‐induced esophageal injury.